The Superb and the Awesome: Animals in Muna-Madan - Devkota, Padma (Literary Studies, 2020)
From the earliest cave painting to the most recent human expressions, both real and fantasized animals have continued to haunt our memory and imagination. Such animals have found their metaphoric, symbolic or metonymic equivalents in our ways of thinking about culture and have largely populated all genres of literature including fables and allegories. They are today invariably tied to our thoughts, motivations and feelings in ways that demand our concern. While we have hunted them or captured and domesticated them for our use, we have also distanced them as inferior beings or stopped to question our own moral superiority over them. However, we have not stopped marveling at the variety and beauty of the animal kingdom with an emotional entanglement which transmutes the wild and dangerous into superb and awesome creations that fill us with wonder and respect. I aim to dwell upon this emotional entanglement to study how Laxmi Prasad Devkota populates his long narrative poem, Muna-Madan, with animals and, in the process, show how these animals reflect the delightful and the tragic mood of the poem.